Prenatal Factors Associated with the Risk of Stunting: A Multilevel Analysis Evidence from Nganjuk, East Java - Indriani, Dewi; Dewi, Lanti Retno; Murti, Bhisma; Qadrijati, Isna (Journal of Maternal and Child Health, 2018)
Background: Globally, one in four children under the age of five suffers from stunting. Stunting is associated with an underdeveloped brain, with long-lasting harmful consequences, including diminished mental ability and learning capacity, poor school performance in childhood, reduced earnings and increased risks of nutrition-related chronic diseases, such as diabetes, hypertension, and obesity in future. This study aimed to analyze prenatal factors associated with the risk of stunting in Nganjuk, East Java, using a multilevel analysis. Subjects and Method: This was an analytic observational study with a case control design. The study was conducted at 25 posyandus (integrated health posts) in Nganjuk, East Java, from June 03 to July 07, 2018. Posyandu was selected by stratified random sampling. A sample of 225 children under five was selected by fixed disease sampling, consisting of 75 stunted children and 150 normal children. The dependent variable was stunting. The independent variables were birth length, maternal height, and family size. The data were collected by questionnaire and analyzed by a multilevel logistic regression run on Stata 13. Results: The risk of stunting increased with maternal height <150 cm (b= 2.59; 95% CI= -0.75 to 4.42; p= 0.006), birth length <48 cm (b=4.17; 95% CI= 2.19 to 6.15; p<0.001), and large family size (b= 2.31; 95% CI= 0.34 to 4.29; p= 0.022). Posyandu had a contextual effect on stunting with ICC= 63.39%. Conclusion: The risk of stunting increases with maternal height <150 cm, birth length <48 cm, and large family size. Posyandu has a sizeable contextual effect on stunting. Keywords: stunting, birth length, maternal height, family size, posyandu, multilevel Correspondence: